2019
DOI: 10.3889/oamjms.2019.459
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin in Combination with Pegylated Interferon and Ribavirin Provided High Rate of Sustained Virological Response in Patients with Genotype 3 Hepatitis C Virus

Abstract: BACKGROUND: Chronic hepatitis C virus infection represents a more frequent cause of liver cirrhosis and hepatocellular carcinoma. Statins, inhibit HCV replication in vitro, enhance the antiviral effect of the already known antiviral drugs and reduce their resistance. AIM: To determine the impact of additional therapy (treatment with Atorvastatin 20 mg) to the standard antiviral therapy (pegylated interferon alpha-peg-IFN α and ribavirin) on achieving sustained virological response (SVR). MATERIAL A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…By running MTT assay & hemagglutination endpoint test, significant anti-influenza properties of atorvastatin in cell culture were ascertained, which may interfere with inhibition of the early stage of virus replication [10] . A previous study has shown that combination therapy with atorvastatin + interferon pegylated alpha + ribavirin results in a high sustained virological response rate (SVR) of 95.83% in patients with genotype 3 chronic hepatitis C, and as a result, statin therapy can be performed with high safety in patients with chronic hepatitis C [11] . The Current guideline for the treatment of COVID-19 inpatients in Iran includes the administration of lopinavir/ritonavir (kaletra) [12] , but atorvastatin has not been tested in hospitalized patients.…”
Section: Introductionmentioning
confidence: 99%
“…By running MTT assay & hemagglutination endpoint test, significant anti-influenza properties of atorvastatin in cell culture were ascertained, which may interfere with inhibition of the early stage of virus replication [10] . A previous study has shown that combination therapy with atorvastatin + interferon pegylated alpha + ribavirin results in a high sustained virological response rate (SVR) of 95.83% in patients with genotype 3 chronic hepatitis C, and as a result, statin therapy can be performed with high safety in patients with chronic hepatitis C [11] . The Current guideline for the treatment of COVID-19 inpatients in Iran includes the administration of lopinavir/ritonavir (kaletra) [12] , but atorvastatin has not been tested in hospitalized patients.…”
Section: Introductionmentioning
confidence: 99%
“…ATO suppresses HCV replication and has synergistic action with interferon. Additionally, it is associated with a 49% reduction in the incidence of hepatocellular carcinoma [69][70][71][72].…”
Section: Hcv In Vitro and Patientsmentioning
confidence: 99%
“…This evidence has been supported by some studies that have shown that statins may have some antiviral potential against HCV. In fact, statins have been shown to have antireplicative viral activity against HCV when used in association with interferon [74][75][76]. By reducing the availability of cholesterol, statins may represent possible candidates to interfere with virus fusion and entry into host cells [77].…”
Section: Statins' Role In Covid-19 Infectionmentioning
confidence: 99%